Microsurgical and endoscopic approaches to the skull base anatomy, tactics, and techniques - Borba, Luis A. B.; Oliveira, Jean G. de (Thieme, 2021)
"A deep knowledge of regional anatomy, improved understanding of pathologies and their behaviors, technological advances, and multidisciplinary collaboration have led to more effective treatments for the once inoperable skull base lesions. Microsurgical and Endoscopic Approaches to the Skull Base: Anatomy, Tactics, and Techniques by renowned skull base neurosurgeons Luis A. B. Borba and Jean G. de Oliveira presents a balanced, anatomy-based perspective on microsurgical and endoscopic approaches to manage these highly challenging lesions. The text leverages the best current scientific literature on this topic and insights from global skull base surgery experts"--